Thermodynamically consistent space-time discretization of non-isothermal mechanical systems in the framework of GENERIC - Georg Schiebl, Mark (Schriftenreihe des Instituts für Mechanik, Karlsruher Institut für Technologie, 2022)
The present work addresses the design of structure-preserving numerical methods that emanate from the general equation for non-equilibrium reversible-irreversible coupling (GENERIC) formalism. Novel energy-momentum (EM) consistent time-stepping schemes in the realm of molecular dynamics are proposed. Moreover, the GENERIC-based structure-preserving numerical methods are extended to the context of large-strain thermoelasticity and thermo-viscoelasticity.